Eliza Haywood’s Female Spectator: Between Literature and Journalism - Tatiana V. Yakushkina (RUDN Journal of Studies in Literature and Journalism)
Eliza Haywood, a famous English novelist of the 18th century, went down in the history of journalism as the author of the first women’s periodical The Female Spectator . Despite Haywood’s prominent contribution to the development of journalism, her experience in this area has remained virtually unnoticed in Russian scholarship. The purpose of this study is to examine the forms of Haywood’s transformation when passing from a novel into a periodical writer with special attention to her ways of interacting with the readers. Based on the prime source and recent English-language research analysis, the author of the article comes to the conclusion that Haywood used a number of strategies when working out her magazine: she creates the images of a collective publisher and a collective reader, implements a program for educating a female audience, and masters new principles of presenting material and interacting with the reader. The necessity of transforming female novel lovers into readers of a new quality required Haywood to use, besides some literary techniques, a number of educational and didactic ones. Thus, she works hard on building up a new attitude to reading, educates the female audience by discussing a range of issues, and searches for a different, eluding obvious didacticism, form of interaction with her audience. Even though most of the material published in the Female Spectator remains of the literary origin, new characteristics of the periodical as a cultural and social control element emerge behind each of the listed techniques.